Pengaruh Karakter Eksekutif, Ukuran Perusahaan, Kualitas Audit, dan Komite Audit Terhadap Tax Avoidance - Pujilestari, Retno; Winedar, Mustika (JURNAL AKUNTANSI DAN AUDITING, 2018)
This study aims to examine the effect of Executive Character, Company Size, AuditQuality, and Audit Committee on Tax Avoidance. Executive Character is measured bycalculating company risk, Company Size is determined based on company size, AuditQuality is stated based on who KAP audits the company, and Audit Committee isdetermined based on the number of Audit Committees in the company. While TaxAvoidance is measured by CETR. By taking samples of mining companies that areactive and listed on the Indonesia Stock Exchange for the period of 2012 to 2016selected by purposive sampling technique, the research data collected throughdocumentation techniques are then analyzed by multiple linear regression and theresults show that Executive Character, Company Size, Quality Audit, and the AuditCommittee simultaneously have a significant effect on Tax Avoidance. But partiallyonly Audit Quality has an effect on Tax Avoidance.